Lean and green? Evidências empíricas do setor automotivo brasileiro - De Sousa Jabbour, Ana Beatriz Lopes [UNESP]; Jabbour, Charbel José Chiappetta [UNESP]; De Souza Freitas, Wesley Ricardo; Teixeira, Adriano Alves (FapUNIFESP (SciELO), 2013)
The aim of this paper is to verify whether the practices of lean manufacturing are positively associated with the adoption of environmental management practices in Brazilian companies in the automotive sector to test the hypothesis that by being lean the business tends to become green. To this purpose, a framework associating these concepts with the research hypothesis was proposed. The data collected from 75 companies were analyzed using Structural Equation Modeling. The main results show that lean manufacturing (LM) is positively associated with environmental management (EM), but the explanation power of LM over EM is considered weak/moderate. In fact, being lean also means being green, but other organizational variables not considered in this study may influence the greening of organizations.
Lean and green? Empirical evidence from the brazilian automotive industry
Keywords: Automotive sector; Brazil; Environmental management; Lean manufacturing